Identified skeletal collections : the testing ground of anthropology? - Henderson, Charlotte Yvette; Cardoso, Francisca Alves (Archaeopress Publishing Ltd, 2018)
Human skeletons are widely studied in archaeological, anthropological, and forensic settings to learn about the deceased. This work focuses on identified skeletal collections and discusses how and why collections were amassed and shows the vital role they play in improving methods and interpretations for archaeological and forensic research.